Penggunaan tongue scraper dan kebersihan gigi dan mulut setelah penyuluhan pada anak Panti Asuhan Ashabul Kahfi Makassar Using tounge scraper and oral-dental hygiene after counseling at children of orphanage Ashabul Kahfi Makassar - Idham Idham; Rifaat Nurrahma; Rasmidar Samad (DiscoverSys Inc., 2013)
Tongue cleaning is a simple and quick procedure to eliminate organisms and debris on tongue. Tongue cleaning canbe performed by using a tongue scraper. This study was conducted to determine the correlation between the index ofOHI-S and tongue coating, and explain the knowledge of oral hygiene and a tongue scraper tongue at an orphanage inMakassar. Subjects were children of orphanage Ashabul Kahfi, who attend and agree to all the procedures. Dentalhygiene assessed by OHI-S index and examination of the tongue by tongue coating index. A total of 24 boys and 16girls were given questionnaires before and after counseling. The results showed no significant correlation between thetwo indices (p=0.382). Distribution of the questionnaire answers showed increased correct answers after givingcounseling. However, based on the level of education and gender, showed no significant differences in knowledgeregarding the cleanliness of the tongue and a tongue scraper (p=0.858, p=0.486). Significant differences were also seen in the comparison group who use and do not use a tongue scraper. It was concluded that there was no significantcorrelation between OHI-S index and tongue coating, but counseling would increase knowledge of the child orphanageAshabul Kahfi although there was no difference in knowledge regarding the cleanliness of the tongue and a tonguescraper based on education level and gender.